Atomically locked interfaces of metal (Aluminum) and polymer (Polypropylene) using mechanical friction. (15th April 2019) - Rout, Arpan; Pandey, Prafull; Oliveira, Eliezer Fernando; da Silva Autreto, Pedro Alves; Gumaste, Anurag; Singh, Amit; Galvão, Douglas Soares; Arora, Amit; Tiwary, Chandra Sekhar
Abstract: Joining different parts is one of the crucial components of designing/engineering of materials. Presently, the current energy efficient low weight automotive and aerospace components consist of a different class of materials, such as metals, polymers, ceramics, etc. Joining these components remains a challenge. Here, we demonstrate metal (aluminum) and polymer (Polypropylene, pp) joining using mechanical friction. The detailed characterization clearly demonstrates that atomically locked interfaces are formed in such joining and no chemical bonds are formed during the joining. Also, a waterproof and strong interface is formed in such a process. Fully atomistic molecular dynamics simulations were also carried out in order to further gain insights on the joining process. Graphical abstract: Image 1074976 Highlights: Demonstrate that mechanical friction can be utilized to form atomically locked interface joints between two different materials (metal and polymer). Atomically locked interfaces formed in such joining result in a waterproof and strong interface. The tensile and bend tests confirm the resistance to fracture due to the interlocking morphology, which exists at macro level and extends all the way to the atomic scale. Fully atomistic molecular dynamics simulations to further gain insights on the joining process.